2016
DOI: 10.3343/alm.2016.36.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the CYP2C19 Phenotype Status and the Results of Three Different Platelet Function Tests in Cardiovascular Disease Patients Receiving Antiplatelet Therapy: An Emphasis on Newly Introduced Platelet Function Analyzer-200 P2Y Test

Abstract: BackgroundAn association has been reported between CYP2C19 polymorphism and the altered antiplatelet activity of clopidogrel. We investigated this association using the newly introduced platelet function analyzer (PFA)-200 (INNOVANCE PFA-200 System; Siemens Healthcare, Germany) P2Y test.MethodsPolymorphisms of CYP2C19*2, *3, *17 and the degree of inhibition of platelet function were determined in 83 patients. Three different platelet function tests were used to evaluate the degree of platelet inhibition and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
12
1
1
Order By: Relevance
“…An increasing number of studies conducted in Asian countries show that reduced function CYP2C19 alleles are associated with an increased risk of vascular events . A recent study by Li et al reported loss‐of‐function CYP2C1P genotype in 59% of Korean patients with cardiovascular disease .…”
Section: Ethnic Distribution Of Cyp2c19 Polymorphisms—is It Clinicallmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies conducted in Asian countries show that reduced function CYP2C19 alleles are associated with an increased risk of vascular events . A recent study by Li et al reported loss‐of‐function CYP2C1P genotype in 59% of Korean patients with cardiovascular disease .…”
Section: Ethnic Distribution Of Cyp2c19 Polymorphisms—is It Clinicallmentioning
confidence: 99%
“…An increasing number of studies conducted in Asian countries show that reduced function CYP2C19 alleles are associated with an increased risk of vascular events. [60][61][62][63] A recent study by Li et al reported loss-of-function CYP2C1P genotype in 59% of Korean patients with cardiovascular disease. 63 Recent data corroborate that patients with CYP2C19 loss-of-function allele CYP2C19*2 are at increased risk for subsequent CVD events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the test was able to identify some non-responders to clopidogrel, identified initially using other approaches, in some groups of volunteers and patients of treated with this drug [71,72]. A further report indicated its usefulness in identifying patients with congenital defective responses to ADP [73] and there is also a correlation with CYP450 genotypes in clopidogrel-treated patients [74,75]. The sensitivity of the test is markedly influenced by the nature of the anticoagulant used in obtaining the blood for analysis [70] and it is likely that this should be taken account of in any future studies.…”
Section: Other Approaches To Assessing Platelet Reactivitymentioning
confidence: 83%
“…However, it is also reported that the genetic polymorphisms of its metabolizing enzyme, cytochrome P450 (CYP) 2C19, are involved in the antiplatelet effect of clopidogrel [4,5]. The CYP2C19 genotypes are classified based on rate of drug-metabolizing activity into three groups: extensive metabolizers (EM), intermediate metabolizers (IM), and poor metabolizers (PM), causing inter-individual variability in response to clopidogrel [6,7]. In addition, prevalence of IM and PM in the Japanese population is higher than in Western populations [6,8].…”
Section: Introductionmentioning
confidence: 99%